Evaluation of the Effectiveness of SEHATI Innovation in Improving the Efficiency of Halal Certification for Micro and Small Enterprises in Indonesia - Veranita, Mira; Turyandi, Itto; Wahyudi, Wahyudi; Gunardi, Gunardi (Universitas Padjadjaran, 2025)
This study aimed to evaluate the effectiveness of the SEHATI (Free and Fast Halal Certification for Micro and Small Businesses) service innovation in improving the efficiency of the halal certification process in Indonesia. The main issue raised is the low efficiency of time, cost, and access to halal certification services, especially for Micro and Small Businesses (UMK). By using a mixed method approach and convergent parallel design, quantitative data was collected through a survey of 71 UMK actors, while qualitative data was obtained through interviews with BPJPH, LPH, and PPH assistants. The results of the analysis showed that time efficiency, cost efficiency, process accessibility, and flexibility do not have a significant effect on service satisfaction. At the same time, qualitative findings reveal various obstacles such as limited digital literacy, hidden costs, and inefficiencies in the field verification process. Although SEHATI has brought about change through digitalization and self-declaration, its implementation has not been fully effective. SEHATI is a strategic innovation with the potential to improve the efficiency of halal certification, yet its implementation still requires improvements in the aspects of assistance, system simplicity, and digital infrastructure so that its benefits are felt evenly and sustainably by MSME actors.